Low medication adherence is associated with decline in health-related quality of life: results of a longitudinal analysis among older women and men with hypertension. Issue 1 (January 2021) - Peacock, Erin; Joyce, Cara; Craig, Leslie S.; Lenane, Zachary; Holt, Elizabeth W.; Muntner, Paul; Krousel-Wood, Marie
Abstract : Objective: The aim of this study was to determine the association of low antihypertensive medication adherence with decline in health-related quality of life (HRQOL) over 1 year. Methods: We used data from older men and women with hypertension ( n = 1525) enrolled in the Cohort Study of Medication Adherence among Older Adults. Adherence was measured using the validated self-report four-item Krousel-Wood Medication Adherence Scale (K-Wood-MAS-4) (low adherence = score ≥1) and prescription refill-based proportion of days covered (PDC) (low adherence = PDC < 0.80). We defined decline in HRQOL as a decrease in Mental Component Summary (MCS) or Physical Component Summary (PCS) score (from the RAND 36-Item Health Survey 1.0 administered at two time points – at the time of adherence assessment and 1 year later) equivalent to the minimal important difference (MID) for each respective summary score, calculated as the average of MID estimates derived from distribution and anchor-based approaches. Results: The prevalence of low adherence was 38.6% using the K-Wood-MAS-4 and 23.9% using PDC. On the basis of mean MID estimates of 4.40 for MCS and 5.16 for PCS, 21.8 and 25.2% of participants experienced a decline in MCS and PCS, respectively, over 1 year. Low adherence was associated with a decline in MCS for K-Wood-MAS-4 [prevalence ratio = 1.32, 95% confidence interval (95% CI) 1.08–1.62, P = 0.008], but not PDC (prevalence ratio = 1.17, 95% CI 0.94–1.47, P = 0.168). Low adherence was not associated with decline in PCS (K-Wood-MAS-4: prevalence ratio = 0.95, 95% CI 0.79–1.16; PDC: prevalence ratio = 1.10, 95% CI 0.90–1.35). Conclusion: Low self-report medication adherence is associated with decline in mental HRQOL over 1 year in older adults with hypertension. Abstract : Supplemental Digital Content is available in the text